Analisis Efektivitas Pelayanan Publik Pada Rumah Sakit Aloe Saboe Provinsi Gorontalo - Nuzlan Botutihe (Publik : (Jurnal Ilmu Administrasi), 2017)
This study aims to determine: (1) the impact of leadership on the effectiveness of health care at the Hospital Aloe Saboe in Gorontalo; (2) the effect of motivation on the effectiveness of health care in Aloe Saboe Hospital in Gorontalo; (3) the impact of infrastructure on the effectiveness of service at Aloe Saboe Hospital in Gorontalo; (4) the effect of leadership, motivation and infrastructure together on the performance of Aloe Saboe Hospital in Gorontalo. The Data and information on the effectiveness of medical care at the Hospital Aloe Saboe was obtained from questionnaires, interviews, observation. The Data were analyzed with descriptive statistics. Conclusion The study showed that: (1) there is an influence on the effectiveness of health care leadership in Aloe Saboe Hospital in Gorontalo; (2) there is a motivational influence on the effectiveness of health care at the Hospital Aloe Saboe in Gorontalo; (3) there are significant infrastructure and facilities on the effectiveness of health care in Aloe Saboe Hospital in Gorontalo; (4) there is the influence of leadership, motivation and infrastructure together on the effectiveness of health care at the Hospital Aloe Saboe in Gorontalo Penelitian ini bertujuan untuk mengetahui : (1) pengaruh kepemimpinan terhadap efektivitas pelayanan kesehatan pada Rumah Sakit AloeSaboe di Kota Gorontalo ; (2) pengaruh motivasi terhadap efektivitas pelayanan kesehatan pada Rumah Sakit Aloe Saboe di Kota Gorontalo ; (3) pengaruh sarana prasarana terhadap efektifitas pelayanan pada Rumah Sakit Aloe Saboe di Kota Gorontalo ; (4) pengaruh kepemimpinan, motivasi dan sarana prasarana secara bersama-sama terhadap prestasi kerja Rumah Sakit Aloe Saboe di Kota Gorontalo. Data dan informasi mengenai efektivitas pelayanan kesehatan pada Rumah Sakit Aloe Saboe ini diperoleh dari kuesioner, wawancara, observasi. Data dianalisis dengan statistik deskriptif. Kesimpulan penelitian menunjukkan bahwa: (1) terdapat pengaruh kepemimpinan terhadap efektivitas pelayanan kesehatan pada Rumah Sakit Aloe Saboe di Kota Gorontalo ; (2) terdapat pengaruh motivasi terhadap efektivitas pelayanan kesehatan di Rumah Sakit Aloe Saboe di Kota Gorontalo ; (3) terdapat pengaruh sarana dan prasarana terhadap efektivitas pelayanan kesehatan pada Rumah Sakit Aloe Saboe di Kota Gorontalo ; (4) terdapat pengaruh kepemimpinan, motivasi dan sarana prasarana secara bersama-sama terhadap efektivitas pelayanan kesehatan pada Rumah Sakit AloeSaboe di Kota Gorontalo